Experimental Study on Carbon Steel Corrosion and its Inhibition Using Sodium Benzoate Under Different Operating Conditions - O.Hassan, Basim; D.Abdul Kader, Huda; F.Abdul-Jabbar, Marwa (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
Corrosion experiments were carried out to investigate the effect of several operating parameters on the corrosion rate and corrosion potential of carbon steel in turbulent flow conditions in the absence and presence of sodium benzoate inhibitor using electrochemical polarization technique. These parameters were rotational velocity (0 - 1.57 m/s), temperature (30oC – 50oC), and time. The effect of these parameters on the corrosion rate and inhibition efficiency were investigated and discussed. It was found that the corrosion rate represented by limiting current increases considerably with increasing velocity and temperature and that it decreased with time due to the formation of corrosion product layer. The corrosion potential shifted to more positive with increasing temperature and velocity while it shifted to more negative with time. Sodium benzoate gave good inhibition efficiency for the whole investigated range of temperature and velocity. Its efficiency was high on clean surfaces and decreased with time in stationary and flow conditions. No noticeable effect of temperature on the inhibition efficiency was noticed.